(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
Modern design of business wear should not only meet the functional requirements, but also meet the fitness and aesthetics requirements. Research done in clothing companies show that unfitness has currently become an obstacle to the development of business wear enterprise. This paper points out the problem and the design needs of an enterprise business jacket. From pattern to design method and ease design as two aspects for further research, it is proposed that based on human characteristics of the business jacket pattern to the design ideas, and through the samples wearing effects, evaluation should be carried out to determine the exact ease and relevant parts that are free of business jacket. This study aims to put forward business jacket pattern designs to provide a new method and for such wear design and distribution of ease to provide a reference basis, which acts as full of theoretical and practical values.